CO2 Emission and Absorption Estimation in Bandung City by Implementing CO2 Emission Rate Reduction Simulation Using the Stella Program - Natalia Christiani; Yayat Hidayat; Sutrisno Trisno (School of Life Sciences and Technology, Institut Teknologi Bandung, 2021)
Bandung CO2 emissions continue to increase in line with its population. The emissions source comes from the industrial, transportation, Liquefied Petroleum Gas (LPG), household, and livestock sectors, whereas CO2 absorption only comes from vegetation through photosynthesis. High CO2 emissions could decrease air quality and reduce environmental health. This study aims to estimate the amount of CO2 emissions and their absorption in Bandung by implementing CO2 Emission Rate Reduction Simulation (CERRS). The simulation comprises four scenarios, namely substitution of vehicle fuel and the application of smart driving techniques, optimization of waste processing in IWPS, processing 90% of livestock waste into biogas, and green space development of 30% of Bandung City area. Estimated CO2 emission and absorption rates were calculated for the next 10 years (2021-2030) using the Stella program version 9.0.2. The results showed that without implementing the CERRS, the amount of CO2 emissions in Bandung in 2030 was estimated to reach 10,983,666.82 tons while implementing the CERRS was 2,361,721.30 tons. Without implementing the CERRS, the estimated amount of CO2 absorptions in 2030 was 214,235.11 tons, while implementing the CERRS was 2,785,703.11 tons. It is expected that the application of the CERRS could reduce the level of CO2 emissions in Bandung by 78.5% and increase CO2 absorptions by 1,200.3%.